Sistem Penunjang Keputusan Seleksi Penentu Atlet Panjat Tebing Ketingkat Pra-Pon Menggunakan Metode Fuzzy - Candrawati, Nuri; Sari, Nova Noor Kamala; Pranatawijaya, Viktor Handrianus (Universitas Palangka Raya, 2021)
KONI Central Kalimantan is a branch of KONI Indonesia. One of the sports in Central Kalimantan is FPTI (Federal Rock Climbing Indonesia). During the decision making on the selection of athlete determinants at the Pre-Pon level, it is carried out by a manual analysis process by considering based on athlete data. To overcome this problem, a system for determining the location of determining athletes at the Pre-Pon level is needed. Therefore, a decision-making system was made using the Tsukamoto fuzzy method. The application of the fuzzy tsukamoto method is in the form of compiling systematic calculations to be carried out, so as to get a value as a comparison material for each athlete. The software development method uses the waterfall where the stages are system analysis and design, database design and interface design, implementation of the Fuzzy Tsukamoto algorithm from design into the PHP and MySQL programming languages ​​as databases, system testing using the Black box method. The application of a decision support system using the Fuzzy Method can help select athletes based on criteria such as endurance, technique, tactics and physicality. The information generated is 15 rock climbing athletes with 5 eligible status and 10 unfit for pre-pound level. The results of the system test show that this application is feasible and can be used according to manual and system trials, which obtained a comparison of 90% of the data with the same results.